Effects of the depth of the acetabular component during simulated acetabulum reaming in total hip arthroplasty - Jianlin Zuo (Nature Portfolio, 2021)
Abstract We aimed to evaluate whether there are differences in the rotation center, cup coverage, and biomechanical effects between conventional and anatomical technique. Computed tomography scans of 26 normal hips were used to simulate implantation of acetabular component. The hip rotation center and acetabular component coverage rate were calculated. Moreover, a finite element model of the hip joint was generated to simulate and evaluate the acetabular cup insertion. Micromotion and the peak stress distribution were used to quantify the biomechanical properties. The medial and superior shifts of the rotation center were 5.2 ± 1.8 mm and 1.6 ± 0.7 mm for the conventional reaming technique and 1.1 ± 1.5 mm and 0.8 ± 0.5 mm for anatomical technique, respectively. The acetabular component coverage rates for conventional reaming technique and anatomical technique were 86.8 ± 4% and 70.0 ± 7%, respectively. The micromotion of the cup with conventional reaming technique was greater than that with anatomical technique. The peak stress concentration was highest in the superior portion with conventional reaming technique, whereas with anatomical technique, there was no stress concentration. Paradoxically although the acetabular component coverage rate is larger with conventional reaming technique, anatomical technique provides less micromotion and stress concentration for initial cup stability. Thus, anatomical technique may be more suitable for acetabulum reaming during primary total hip arthroplasty.